The Expansion of CD25highIL-10highFoxP3high B Regulatory Cells Is in Association with SLE Disease Activity - Zahava Vadasz; Regina Peri; Nasren Eiza; Gleb Slobodin; Alexandra Balbir-Gurman; Elias Toubi (Journal of Immunology Research)
B regulatory cells (Bregs) belong to a subgroup of activated B cells tasked with maintaining self-tolerance and preventing autoimmunity. While sharing similar regulatory mechanisms such as IL-10 dependency, they also defer in exhibiting their suppressive effects by expressing Fas-Ligand, TGF-beta, and PDL-1. In this study we show, for the first time, the expansion of CD25highFoxP3high Bregs in systemic lupus erythematosus (SLE) patients compared to healthy individuals (18.5 ± 3.052% versus 11.0 ± 1.654%, p<0.001, resp.). This expansion was also shown to correlate with SLE disease activity (r=0.75). In addition, CD25highFoxP3high Bregs were also IL-10high expressing and further expanded when stimulated with semaphorin 3A. In sum we show that CD25highFoxP3high are an additional subtype of Bregs, involved in regulating SLE disease activity. Being IL-10 expressing, we may assume that they are one of the sources of increased serum IL-10 in SLE patients. Further studies are required in order to assess the relation between high serum IL-10 and CD25highFoxP3high Breg cells.